2020
DOI: 10.1158/0008-5472.can-19-2691
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with CD68 and Regulation of GAS6 Expression by Endosialin in Fibroblasts Drives Recruitment and Polarization of Macrophages in Hepatocellular Carcinoma

Abstract: ◥Fibroblasts and macrophages play key roles in the development of hepatocellular carcinoma (HCC). However, cross-talk between these two kinds of cells has not been well studied. Endosialin (CD248/TEM1) is a transmembrane glycoprotein that is expressed in certain cancer cells, tumor stromal cells, and pericytes. In this study, we found that endosialin is mainly expressed in cancer-associated fibroblasts (CAF) in HCC and its expression inversely correlates with patient prognosis. Endosialin interacted with CD68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 47 publications
0
67
0
Order By: Relevance
“…In our previous study, we found that PSMA and CD248 were both expressed specifically in the vasculature in hepatocellular carcinoma (HCC), and vascular-expressed PSMA and CD248 might be used as prognostic markers and vascular therapeutic targets for HCC ( 30 , 31 ). We also found that overexpression of CD248 in renal cell carcinoma (RCC) was related to poor prognosis ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that PSMA and CD248 were both expressed specifically in the vasculature in hepatocellular carcinoma (HCC), and vascular-expressed PSMA and CD248 might be used as prognostic markers and vascular therapeutic targets for HCC ( 30 , 31 ). We also found that overexpression of CD248 in renal cell carcinoma (RCC) was related to poor prognosis ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 CD248 was initially identified on blood vessels of various human tumors and was subsequently defined as an abnormally expressed marker of tumor endothelial cells, 9 involving in the reorganization of tumor blood vessels. 10 Recently, emerging observations indicate that CD248 is also expressed in non-endothelial perivascular cells, such as pericytes, 11 fibroblasts, 12 mesenchymal cells, 13 and CD8+ T cells, 14 arguing that CD248-mediated actions are not confined to vascular endothelial cells but rather may extend to vascular remodeling/inflammation process. So far, the functions of CD248 in human vascular pathologies remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the activation of MERTK increased the production of antiinflammatory cytokines [151]. It is worth noting that Gas6 is produced and released from cancer-associated fibroblasts and M2 macrophages, suggesting a positive feedback loop that drastically reinforces the immunosuppressive environment in tumors [153].…”
Section: The Role Of Mertk In Efferocytosismentioning
confidence: 95%